Models of Management: Work, Authority, and Organization in a Comparative PerspectiveModels of Management: Work, Authority, and Organization in a Comparative Perspective, by Guillen Mauro F. Chicago: University of Chicago Press, 1994. - Heydebrand, Wolf (Academy of Management Review, 1997)
The article reviews the book ?Models of Management: Work, Authority and Organization in a Comparative Perspective,? by Mauro F. Guillen.